Life and thought in the ancient Near East - Orlin, Louis L. (University of Michigan Press, 2007)
Machine generated contents note:Mesopotamia --In the Tablet Houses of Mesopotamia --New Year's Day in Babylon --Decoding the Hammurabi Law Code --On the Lighter Side of Mesopotamia: A Glimpse into Sumerian Palace and Temple Household Life --Wild Animals and Game Parks --Archaeology: The "Cold Case File" of the Historian --Egypt --Theme and Variations on Herodotus's Statement That "Egypt Is the Gift of the Nile" --On the Essential Cosmic Rhythms of Ancient Egyptian Life --Palestinian Corridor --Seagoing Phoenicians --From Tribal Coalition to Statehood in Ancient Israel --Ancient Persia and a Tale of Two Cities: Athens and Jerusalem in the Fifth Century --On Nomads and Nomadism --Anatolia --Old Assyrian Trading Enterprise in Asia Minor --On Chariot Warfare --Some Observations on Ancient Near Eastern Treaties --When Princes Squabble: A Royal Dispute in Central Anatolia --Some Literary Observations --On the Greatness of Gilgamesh as an Ancient Near Eastern Epic --Reflections on Ancient Near Eastern Myth --Wisdom Literature --Translating an Old Babylonian Poem: "Prayer to the Gods of Night" --Physical Background: Landforms, Climate, and Hydrology of the Near East --Historical Background: The Setting of Prehistoric Cultural Development in Mesopotamia and Egypt --Civic Background: Cities and Gods in the Ancient Near East -- Mesopotamia, Egypt, and Israel --Languages and Literature --Brief Note on Languages --General View of Ancient Near Eastern Literature --Decipherments --Decipherment of Cuneiform Writing --Discovery of Hittite Civilization and the Decipherment of Hittite --Conclusion: Who Will Know about Us When We're Gone? --Summary of Culture Growth in Mesopotamia and Egypt.